Analysis of the banana packing process for the use of water resources through discrete event simulation - Orozco-Irola, Carlos (2022)
The water resource is an essential element for the banana packing and its availability in some sectors is being limited by the increase in demand, aggravated by the consequences of climate change, so it was correct management of the resource is essential to ensure its quantity, quality and continuity of the banana industry. This research analyzes the current water consumption of a banana packing plant located in the Atlantic zone of Costa Rica, to determine the design alternatives and changes in work procedures the favor its efficient and sustainable use. A characterization of the production process was carried out through a SIPOC diagram, which allowed the identification of nine sub-processes that are directly related to the consumption and use of the resource. Using the 49 days process records, two discrete event simulation models were created, the validation of which shows that, with 95% confidence, that there are no significant differences with respect to the results generated by the model and those obtained from the real process. A current consumption of 96 liters per packed box was obtained for weekdays and 177 liters per packed box for Saturdays. Therefore, applying the simulation models again with the modifications in the design and work procedures, a reduction of 19% in the indicator is estimated for weekdays and 10% for Saturdays, representing an approximate annual saving of 44.777,2 m3 of water.